qurtub.my.id: Website Innovation as a Nahw Learning Media at Ar-Rohmah Integral High School of Malang - Richard, Muhammad Haddad; Thoyyibah, Anisatu (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This research aimed to develop innovative learning media based on the qurtub.my.id website in Nahw learning, which made it easier for students to understand materials, questions and Arabic texts . The problem in this research was that the Nahw learning media used at Ar-Rohmah Integral High School of Malang still used less interesting learning media. This research method used Research and Development using the ADDIE development model, which consisted of five stages, namely, analysis, design, development, implementation, and evaluation. The instruments used in this research were questionnaires, product feasibility sheets for material experts, language experts, and media experts, as well as assessments for Ar-Rohmah Integral High School students. Data collection methods comprised observation, interviews, and questionnaires. The research results indicated that, during the analysis stage, observation, interviews with subject teachers, and literature review were conducted. The design stage produced flowcharts, user interfaces, and user experience. During the development stage, product designs were created using Figma, and websites were built using HTML, CSS, and JavaScript. The implementation stage, namely conducting product trials by material experts, resulted in a presentation score of 76% with valid criteria, while the presentation score was 76% from linguists with valid criteria and a value presentation of 52% from media experts with quite valid criteria. The final stage was an evaluation of conducting trials on students who got a presentation score of 82.93% with very valid criteria. Based on the results above, it can be concluded that overall, the developed product was "very suitable" for use in the learning processes.